Longitudinal changes in optical coherence tomography angiography before and after surgery for acute primary angle closure glaucoma - Ke Yin; Haomin Chen; Yanxin Zhang; Xinyi Li; Ruihong Su; Yi Yue; Yingjuan Lv; Lijie Dong; Yi Shi; Aihua Liu (Photodiagnosis and Photodynamic Therapy, 2025)
Purpose: This study explored changes in retinal microvasculature in patients with Acute Primary Angle Closure (APAC) before and after surgery, assessing their correlation with variations in retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer (GCIPL) thickness, while also examining the effects of acute intraocular pressure elevation on ocular microvasculature. Patients and methods: This was a retrospective longitudinal study that assessed 22 APAC eyes undergoing phacoemulsification, intraocular lens implantation, and trabeculectomy, along with 22 healthy fellow eyes. Optical coherence tomography angiography was used to evaluate vessel density (VD) in the optic disc and macula preoperatively, and at one week and one month postoperatively. The thicknesses of RNFL and GCIPLwere also measured. Results: Postoperatively, the superficial vascular complex (SVC) VD, including the whole image VD (wiVD) of disc and macula, continued to decrease at one month (p < 0.001, p = 0.001). In contrast, at the deep vascular complex (DVC) level, only disc wiVD showed significant changes at one month (p = 0.007). Changes in disc and macula wiVD at the SVC level were significantly correlated with changes in RNFL and GCIPL thickness (p = 0.004, p < 0.001; p = 0.018, p = 0.002), whereas VD at the DVC level was not. The SVC disc wiVD (AUROC=92.56 %) had superior diagnostic performance compared to the DVC disc wiVD (AUROC=58.06 %). Conclusions: We found acute intraocular pressure elevation has lasting effects on APAC eyes. Postoperative alterations in SVC VD seem to be more sensitive indicators for APAC patients.